The Degree of Practice of Mathematics Teachers in the Secondary Stage of E-Learning Skills in Palestine in light of the COVID-19 pandemic - Ziada, Rana Ahmad (Journal of Educational and Psychological Sciences, 2020)
The aim of this study is to identify the degree of practice of mathematics teachers in the secondary stage of e-learning skills in Palestine (in light of the pandemic Covid-19), and the effect of gender, educational qualification and teaching experience variables on the degree of practice. To achieve the goals of the study, the researcher followed the descriptive approach, and a sample consisting of (80) male and female teachers. The study tool consisted of a questionnaire consisting of (34) paragraphs distributed in four fields: the field of "e-learning technology skills", the field of "E-search skills)", the field of "e-learning management", and the field of "e-learning evaluation". And the results of the study showed that the degree of mathematics teachers' practice in the secondary stage of e-learning skills in light of the Covid-19 pandemic came with a medium degree with an average of (2.96) and a percentage of (59.2%). The degree of teachers ’practice in all fields came with an average degree, and the field of e-learning techniques got the first rank with an average (3.33) with a percentage of (66.6%), and the second ranking came in the field of electronic search with an average of (3.28) and a percentage of (65.6%), and the field of e-learning management ranked third with an average of (2.74) and a percentage of (54.8%), and The fourth ranking came in the field of e-learning evaluation, and it got an average of (2.50) and at a percentage of (50%). The results also showed that there were statistically significant differences attributable to the gender variable in all fields except for the field of e-learning management skills, and the differences came in favor of males, as the results showed that there are statistically significant differences attributable to the variable of the academic qualification in the fields of skills of e-learning techniques, e-search skills, and for the benefit of high graduate studies holders, and the results also showed the presence of statistically significant differences attributable to the variable of teaching experience in the field of e-learning management skills and the field of electronic evaluation, and in the field of e-search skills, and in favor of higher teaching experience (five years or more), the study recommended the necessity of holding training courses for high school mathematics teachers in Palestine to build the capacity of teachers in e-learning skills.
Keywords: E-learning; Secondary level; Mathematics teachers